Evaluation of Maize (Zea mays L.) Varieties in Selected Lowland Areas of Southern Ethiopia - Tariku Simion Dojamo; Selamawit Markos Takiso; Melese Lema Tessema (International Journal of Agronomy)
Drought and high temperature are among the major factors limiting maize productivity in Sub-Saharan Africa. An increase in temperature above 30°C reduces yield by 1% under optimal rain-fed conditions. Approaches that improve performance under drought and high temperatures are essential to sustain productivity. The objectives of this study were to evaluate the performance of improved maize varieties released for lowland areas and to select better-performing varieties to address climate-crosscutting issues. Eight lowland maize varieties at two locations for two years were tested by using a randomized complete block design during the 2017 and 2018 cropping seasons. Analysis of variance revealed significant differences (p<0.05) between varieties for all the studied variables over years across locations. The interaction of locations with varieties was nonsignificant for grain yield, cob length, and cob number. The mean grain yield indicated that the variety Melkassa-6Q is a high yielder compared to others with 3284 kg grain yield per hectare. This variety had a 35% yield advantage over the check. The variety is, therefore, highly recommended in the study areas.